Penguatan Komitmen P3DN Dalam Rangka Perizinan Penggunaan Produk Impor Di Pemerintahan Kabupaten Garut - Adam, Wahyu; Somadi (CV. SINAR HOWUHOWU, 2025)
In this era of globalization, activities aimed at meeting increasing market needs sometimes force the government to import products. The government imports many goods to support the Indonesian economy in various fields such as infrastructure, industry, health, and others. This is due to the limitations of technology, the quality and quantity of products. The Indonesian government itself has created the Domestic Product Use Improvement (P3DN) to maximizing the use of domestically produced products. The purpose of this study is to determine P3DN commitment, and strategies undertaken to strengthening P3DN commitment in the Garut City local government environment. In addition, this research is also to find information about the licensing procedures for using imported products if domestic products do not meet the criteria or quantity needed by an local goverment. This research uses a qualitative approach by conducting in-depth interviews, field observations, and collecting secondary data from trusted sources. The results showed that the P3DN commitment of the Garut City government was very high. The obstacles on strengthening this P3DN commitment are the absence of local products that can substitute imported products, this still dominate in several fields. In addition, the quality and quantity that have not met the standards are also an obstacle to this P3DN program that cannot be equalized. The P3DN team of Garut City often conducts socialization and e-catalog optimization to increase the use of domestic products in the Garut City government. This research also obtained information related to licensing the use of imported products if there are no domestic products that meet the needs